Beautiful days : stories - Williams, Zach, (Zachary Conner), 1984- (Doubleday, 2024)
"From New Yorker and Paris Review contributor and Wallace Stegner Fellow Zach Williams comes a staggering debut story collection that confronts parenthood, mortality, and life's broken promises. Parents awaken in a home in the woods, again and again, to find themselves aging as their toddler remains unchanged. An employee is menaced by a conspiracy-minded security guard and accused of sending a sinister viral email. An aging tour guide leads a troublesome group to the site of a UFO, witnessing the slow social deterioration as the rules of decorum go out the window. In each of Williams' ten stories, time is as fallible as the characters, and reality is witnessed through the gauzy folds of a dream--or a nightmare. Bucolic scenes devolve into harrowing exercises in abandonment; the quotidian nature of office life raises serious questions of existential fortitude. Williams is keenly aware of the insidiousness lurking in the shadows of the everyday, ably spiking it with humor. He depicts the divided self of the parent, the distances necessary to protect our children, and the fallout of our deepest relationships. Williams sees the perversity in the mundane and dares readers to recognize the impact--and beauty--of time's relentless movement. With exquisite prose and a lacerating wit, Beautiful Days holds a mirror to the many absurdities of being human and refuses to let us look away"--